2019
DOI: 10.3390/act8010028
|View full text |Cite
|
Sign up to set email alerts
|

Modified U-shaped Microactuator with Compliant Mechanism Applied to a Microgripper

Abstract: In this paper, a modified U-shaped micro-actuator with a compliant mechanism is proposed. It was analyzed with a uniform and modified thin arm, as well as a similar variation in the corresponding flexure, in order to observe the impact of the compliant lumped mechanism. The use of these compliant mechanisms implies an increment in the deformation and a reduction in the equivalent stress of 25% and 52.25%, respectively. This characterization was developed using the Finite Element Method (FEM) in ANSYS Workbench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Bu çalışmada, mikro-aktüatörün tasarım sürecinde U tipi aktüatör referans alınmıştır. U-tipi mikro-aktüatör, birçok uygulamayı tasarlamak ve oluşturmak için kullanılan karakteristik bir MEMS cihazıdır [43]…”
Section: Tasarım Koşulları (Design Conditions)unclassified
“…Bu çalışmada, mikro-aktüatörün tasarım sürecinde U tipi aktüatör referans alınmıştır. U-tipi mikro-aktüatör, birçok uygulamayı tasarlamak ve oluşturmak için kullanılan karakteristik bir MEMS cihazıdır [43]…”
Section: Tasarım Koşulları (Design Conditions)unclassified
“…In other words, large output forces can be produced by applying relatively low voltages (below 10 V) [13,14]. Electrothermal actuators have been widely deployed for microgripping applications [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…They include actuators and gripping arms made of thin silicon or stainless sheets, which are used to produce sufficient strength. Several research studies have reported on the design and performance analysis of microgrippers [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The design aspects of these microstructures include the kinematic structure [18,24], the material selection [21,24], the actuation mechanism [16], the fabrication process [17,20], and the impact of the surrounding environment on their operation [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enduring trend [2], together with the consequent evolution of massive low-cost and large-scale semiconductor and microelectronics technologies [3], also triggered the conception and manufacturing of micromechanical structures [4], paving the way to the birth and growth of Micro Electro-Mechanical Systems (MEMS) [5][6][7][8]. MEMS can be used as extremely miniaturized sensors, actuators, microgrippers [9][10][11], with different sorts of actuation [12][13][14], piezoelectric resonators [15,16], and wave-guides [17], to only name but a few. They share with microelectronic devices the same conceptual platform: processes, technologies, and facilities able to produce low-cost, large-volume fabrication steps [18,19].…”
Section: Introductionmentioning
confidence: 99%